Pengaruh Konten Marketing Media Sosial Tiktok terhadap Keputusan Pembelian Konsumen Shopee di Kota Jambi - Ambok Pangiuk; Dea Ayu Cahyani (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The tiktok application has been downloaded more than 100 million. Along with the number of tiktok users, this application can help increase engagement, one of which is the trend of shopee poison or shopee haul that has been created by content creators and some are viral and have the highest number of viewers. Shopee is a buying and selling application that offers a variety of products ranging from fashion products to daily necessities. The purpose of this study was to determine the effect of social media tiktok on consumer purchasing decisions at shopee. The method used in this research is descriptive quantitative method. Data collection techniques used in this study were observation, questionnaires and documentation. The results of this study indicate the influence of the use of social media tiktok on purchasing decisions at shopee (Study in Mayang Mangurai Village, Alam Barajo District, Jambi). With the results of the influence of the use of social media tiktok on purchasing decisions at shopee by 45.0%, while the remaining 55.0% is influenced by other variables not examined in this study.